The effect of smart fertigation systems on chilli grown in a greenhouse for urban farming - Cui, Hairu; Hanafi, Marsyita; Fazlil Ilahi, Wan Fazilah; Zamri, Mohd Amir Sabrin; Shafie, Siti Mariam; Mashohor, Syamsiah (John Wiley and Sons, 2022)
Reasonable fertigation methods are essential for plant growth, as excessive or inadequate water and fertilizer supply can lead to plant diseases, resource consumption, or even crop production reduction. These problems are common to local farmers in Malaysia, especially for large-scale chilli cultivation using traditional irrigation approaches in rural areas. These problems need to be addressed, as chilli are one of Malaysia's high-cash crops with massive local demands. Realizing an efficient irrigation control approach using an innovative fertigation method is a potential solution to tackle such problems. This paper proposes a smart fertigation system for chilli cultivation in greenhouses in urban areas to increase chilli production and improve irrigation management. The proposed system utilized the fuzzy logic method for intelligent irrigation decisions, where the decision is based on the input data provided by soil moisture, temperature, and humidity sensors. In addition, the proposed system can monitor and control irrigation in the greenhouse remotely through a website that was developed using the Hostinger platform. The results showed that the fuzzy-based fertigation approach produced approximately 50% irrigation application efficiency and a higher growth gradient and chilli yield than the traditional approach in both cycles.